1979
DOI: 10.1111/j.1432-1033.1979.tb19754.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ATP-Supported and GTP-Supported Phosphate Turnover of the Calcium-Transporting Sarcoplasmic Reticulum Membranes

Abstract: The study deals with the interrelationship of the phosphate-transferring activities of the calciumtransporting sarcoplasmic reticulum membrane vesicles : the phosphate exchange between nucleoside triphosphate (NTP) and nucleoside diphosphate (NDP) (NTP-NDP exchange), the calcium-dependent NTPase, and the phosphorylation of NDP by inorganic phosphate in the presence of NTP (NTP-Pi exchange). Different nucleotides were used as phosphate donors and acceptors. It is demonstrated for the phosphate transfer from ITP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1981
1981
1987
1987

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…It was found that ATP-ADP exchange is 4 to 10 times faster than the rate of calcium exchange (Waas and Hasselbach, 1981;Takenaka et al, 1982), while GTP-GDP exchange approximately matched calcium exchange (Ronzani et al, 1979). Ronzani et al (1979) therefore called into question the coupling of nucleotide diphosphokinase activity and calcium translocation. Takenaka and co-workers (1982) conclude ".…”
Section: Introductionmentioning
confidence: 99%
“…It was found that ATP-ADP exchange is 4 to 10 times faster than the rate of calcium exchange (Waas and Hasselbach, 1981;Takenaka et al, 1982), while GTP-GDP exchange approximately matched calcium exchange (Ronzani et al, 1979). Ronzani et al (1979) therefore called into question the coupling of nucleotide diphosphokinase activity and calcium translocation. Takenaka and co-workers (1982) conclude ".…”
Section: Introductionmentioning
confidence: 99%
“…Sarcoplasmic reticulum vesicles were prepared according to the procedure described by Hasselbach [31]. Calciuiii uptake was determined in the presence of 5 mM potassium oxalate by the Millipore filtration technique using the same buffer as described above, except A-231 87 was omitted.…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…The rate of ATP-ADP-exchange is also inhibited at relatively high C a2+ con centrations [27] and the inhibition range depends on the Mg2+ concentration in the assay (Fig. 7).…”
Section: P =mentioning
confidence: 99%